Awareness: The effect of group counseling on awareness and acceptance of self and others - ERDEN ÇINAR, SEVAL (ELSEVIER SCIENCE BV, 2015)
In this research, the effect of raising awareness-oriented group counseling programme, predominated by cognitive behavioral methods, on self-awareness, cognitive structures, emotion regulation, and relationships of university students has been investigated. Study design is pre-post test, experiment and control group model. Self-reflection and Insight Scale, Cognitive Emotion Regulation Questionnaire, and Automatic Thoughts Questionnaire were used as instruments. Mann-Whitney U test and Wilcoxon signed ranks test was used in the data analysis. The results showed that the programme was significant on the self-awareness, automatic thoughts, and emotion regulation. It can be concluded that the training programme may have permanent effects. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Self-awareness; Automatic Thoughts; Cognitive Emotion Regulation; Group Counseling; University Students